A Critical Review on the article “Investigation of the Establishment and Decline of Āl-Shomleh Local Government (550-591 AH) In Seljuk Khuzestan” - Mohsen Rahmati (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This study critically examines the article "Investigation of the Establishment and Decline of Āl-Shomleh Local Government (550-591 AH) In Seljuk Khuzestan" from both positive and negative perspectives. By adopting the title of "Atabak" or "Great Atabak", the dynasty of Shumleh established a local government in important and strategic areas of west and southwestern Iran (between the territories of the Seljuq sultans and the Abbasid caliphate). It is of special importance to know this less famous dynasty. The article under review, which was introduced as the first independent research work, was a kind of the beginning of a new trend in research in this field. The findings of this research show that one of the advantages of the article under review is the importance of the subject and the effort to process the matter differently, but one can also see some formal and methodological shortcomings such as incorrect references, inconsistencies in title and content, inattention to the background of the research, neglect of some main sources, inattention to the criticism and validation of traditions, use of definitive and absolute propositions, be weak in arguments and inferences, and have errors in identifying the members of the Shumleh family.